Physiotherapists’ perspectives on the implementation of direct access to physiotherapy services in Saudi Arabia: a cross-sectional study - Hosam Alzahrani; Razaz Shaheen; Osama Mohammed; Elaf Marouf (BMJ Open)
Objective This study investigates Saudi Arabian physiotherapists’ perspectives on direct access to physiotherapy (DAPT) services, focusing on perceived benefits, barriers and implementation in clinical practice.Methods A cross-sectional observational study design was used. Data collection occurred between December 2022 and June 2023 via an online structured questionnaire distributed through email and text messages. The DAPT section comprised items on awareness, endorsement, obstacles/barriers to implementation in Saudi Arabia, perceived benefits and expected benefits of various resources to guide evidence-based practice for physiotherapists. This section featured closed-ended questions using a 5-point Likert scale. The study included licensed physiotherapists currently working in Saudi Arabia.Results The study included 401 participants, with a nearly equal distribution of 203 males (50.6%) and 198 females (49.4%). The most common age group was 25–34 years, comprising 70.6% of the participants. A significant proportion (61.6%) were aware of DAPT, and 88% acknowledged its potential to reduce delays in care. However, 49.9% had not engaged with relevant literature. The primary barriers to DAPT identified were laws and regulations (mean=3.69, SD=1.21), physician support (mean=3.59, SD=0.99), entry-level education (mean=3.45, SD=1.17), patient beliefs (mean=3.38, SD=1.24), self-confidence (mean=3.35, SD=1.15) and professional autonomy (mean=3.34, SD=1.22).Conclusion Physiotherapists in Saudi Arabia demonstrate substantial awareness of direct access. Organisational initiatives and increased awareness are essential to promote direct access. This study highlights that direct patient access to physiotherapists offers significant benefits to patients, healthcare workers and the broader community.